2008
DOI: 10.1242/jeb.020164
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical properties of consecutive layers in specialized insect cuticle: the gula ofPachnoda marginata(Coleoptera, Scarabaeidae)and the infrared sensilla ofMelanophila acuminata(Coleoptera,Buprestidae)

Abstract: SUMMARYInsect cuticle is a highly adaptive material that fulfils a wide spectrum of different functions. Cuticle does not only build the exoskeleton with diverse moveable parts but is also an important component of a stunning variety of mechanosensory receptors. Therefore, the mechanical properties of these specialized cuticular systems are of crucial importance. We studied the different cuticular layers of the head part (gula) of the head-to-neck ball articulation of Pachnoda marginata and of the photomechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 27 publications
(45 reference statements)
3
31
0
Order By: Relevance
“…Andersen showed that secondary reactions caused by removal of water from the insect cuticle play a dominant role in contributing to the stiffness of the material as compared with processes that remove phenols through chemical treatment (Andersen, 2010). In this study, we prepared ovipositors for mechanical experiments using an ethanol dehydration procedure that leads to a stiffer material response compared with native fresh insect cuticle (Müller et al, 2008;Barbakadze et al, 2006;Schofield et al, 2002;Klocke and Schmitz, 2011). Ethanol storage of insect specimens was, however, unavoidable because of limitations with acquiring insects and in sample preparation for measurement of mechanical properties using AFM.…”
Section: Materials Properties Of Pollinator and Parasitoid Ovipositorsmentioning
confidence: 99%
“…Andersen showed that secondary reactions caused by removal of water from the insect cuticle play a dominant role in contributing to the stiffness of the material as compared with processes that remove phenols through chemical treatment (Andersen, 2010). In this study, we prepared ovipositors for mechanical experiments using an ethanol dehydration procedure that leads to a stiffer material response compared with native fresh insect cuticle (Müller et al, 2008;Barbakadze et al, 2006;Schofield et al, 2002;Klocke and Schmitz, 2011). Ethanol storage of insect specimens was, however, unavoidable because of limitations with acquiring insects and in sample preparation for measurement of mechanical properties using AFM.…”
Section: Materials Properties Of Pollinator and Parasitoid Ovipositorsmentioning
confidence: 99%
“…We were able to show that the specialized layering of the flagellar exo-and endocuticle, and in particular the water content, significantly affects its biomechanical properties. As the compliance of endocuticle is thought to be due to its high water content (Mueller et al, 2008;Vincent and Wegst, 2004), this indicates a critical role of the endocuticle.…”
Section: Histology Of the Flagellummentioning
confidence: 99%
“…Over the past 60years, different insect species and body parts have been tested by engineers and biologists, using various techniques, and it has been shown that the Young's modulus of cuticle can range from less than 1kPa (intersegmental membranes of mature female locusts) to several GPa (tendons) (Vincent and Wegst, 2004). It has also been shown experimentally that variations of the cuticle's fibre alignment, water content and controlled 'tanning' of the material affect the cuticle's static mechanical properties, such as stiffness and hardness, and dynamic mechanical properties, such as damping, over several orders of magnitude (Müller et al, 2008;Klocke and Schmitz, 2011;Dirks and Dürr, 2011;Schöberl and Jäger, 2006;Göpfert and Robert, 2001).…”
Section: Introductionmentioning
confidence: 99%